Features of coping behavior in divorce situations among men and women - O. I. Mironova; M. S. Sovzikhanova (Вестник университета, 2025)
This article examines the results of studying the specifics of coping strategies employed by men and women during divorce. Dissolution of marriage is a highly stressful life event with potential adverse impacts on both physical and psychological well-being, which contributes to the appearance of coping behaviour for further adaptation of an individual. When determining types of the coping strategies, we have chosen the classification of C.S. Carver, M.F. Scheier, and J.K. Weintraub, who are the developers of the questionnaire “Coping Orientation to Problems Experienced Inventory”. According to the results of the statistical data analysis using the Mann-Whitney U-test, it has been revealed that men tend to employ behavioural disengagement strategies more frequently, whereas women lean towards seeking emotional social support. Moreover, thematic analysis of semi-structured interviews unveils specifics of the coping behaviour at individual level and additional coping strategy, notably non-religious spiritual practices that necessitates further empirical validation. Additionally, the study observes that psychological experience of the divorce situation is most intense in the first two years, and the behaviour is aimed at accepting the situation and coping with distress. These features should be considered in practical work with people who are divorced.